Governance and fiscal decentralisation in Latin America: An empirical approach - Diego E. Pinilla; Patricia Hernández-Medina (Economies, 2024)
The objective of this study was to establish the relationship between certain institutional variables and the effectiveness of fiscal decentralisation in Latin America. To fulfil this objective, we took a sample of 15 Latin American countries for the years 1996 to 2020 to estimate the logarithm of GDP per capita based on the level of fiscal decentralisation, as well as its interaction with six institutional variables plus three control variables. The results show that institutional variables always modulate the effects of fiscal decentralisation, in most cases significantly and negatively, the exceptions being accountability with a positive result and government effectiveness with a non-significant result. It was concluded that in the presence of weak regulations, political conflicts, and corruption, fiscal decentralisation can worsen social or economic circumstances in Latin America.
Keywords: 330; economic growth; panel data; accountability; corruption; fiscal decentralisation; governance